Determination of extreme sea levels along the Iberian Atlantic coast. (1st January 2016) - Fortunato, André B.; Li, Kai; Bertin, Xavier; Rodrigues, Marta; Miguez, Belén Martín
Abstract: Extreme sea levels along the Atlantic Iberian coast are determined through the development and application of a numerical model for tides and surges, followed by a statistical analysis of the model results. A recent statistical method is assessed using 131 years of data from the Brest tide gauge, and the number of years of data required for an accurate statistical analysis is estimated. The statistical method is extended to consider tide–surge interactions, but they are shown to be small in the study region. The model covers a large portion of the NE Atlantic, with a 250 m resolution in the Portuguese shelf. In the Iberian shelf, root mean square errors of tides are of the order of 5 cm, and extreme sea levels are underestimated by about 10 cm. Differences between sea level statistics obtained from model output and observations are of the order of 5 cm in the study region. Simulation of tides and surges between 1980 and 2010, followed by a statistical analysis of the results, provide the extreme levels along the Iberian Atlantic coast for different return periods. Results reveal the increase of extreme sea levels from south to north and the importance of local effects. Highlights: Statistical method to determine extreme sea levels described and analyzed. Tides and surges are hindcast in the NE Atlantic for 1980–2010. Extreme sea levels along the Iberian Atlantic coast determined by statistical analysis. Extreme sea levels increase northward and inside sheltered bays.